An updated overview of diabetic nephropathy: Diagnosis, prognosis, treatment goals and latest guidelines. (8th April 2020) - Selby, Nicholas M.; Taal, Maarten W.
Abstract: Diabetic nephropathy (DN) is a major healthcare challenge. It occurs in up to 50% of those living with diabetes, is a major cause of end‐stage kidney disease (ESKD) that requires treatment with dialysis or renal transplantation, and is associated with significantly increased cardiovascular morbidity and mortality. DN is a clinical syndrome characterized by persistent albuminuria and a progressive decline in renal function, but it is increasingly recognized that the presentation and clinical course of kidney disease in diabetes is heterogeneous. The term diabetic kidney disease (DKD) is now commonly used to encompass the spectrum of people with diabetes who have either albuminuria or reductions in renal function. In this article, the clinical presentation and approach to diagnosis of DKD will be discussed, as will its prognosis. The general principles of management of DKD will also be reviewed with reference to current international guidelines.